Subsolidus phase equilibria and electrical properties of pyrochlores in the Bi2O3–CuO–Ta2O5 ternary system - Chon, M. P.; Tan, Kar Ban; Khaw, Chwin Chieh; Zainal, Zulkarnain; Yap, Taufiq Yun Hin; Chen, Soo Kien; Tan, P. Y. (Elsevier, 2016)
Subsolidus phase relations had been determined for the Bi2O3–CuO–Ta2O5 (BCT) system over the temperature range 700–950 °C in air. Two structurally distinct ternary phases of different symmetries, a cubic pyrochlore and a monoclinic zirconolite were observed. Phase-pure pyrochlores existed in a unique boomerang-shaped area, which could be described using the general formula, Bi2.48+yCu1.92−xTa3.6+x−yO14.64+3x/2−y: 0.00(1) ≤ x ≤ 0.80(1) and 0.00 (1) ≤ y ≤ 0.60(1), respectively. BCT subsolidus pyrochlores exhibited low electrical conductivities, 10−7–10−6 S cm−1, moderate dielectric constants, ε′, ∼60–80 and low dielectric losses, tan δ, ∼0.01–0.20 at 1 MHz and ambient temperature, ∼28 °C. The recorded low activation energies, 0.32–0.40 eV suggesting these electroceramics were of semiconductor-type at elevated temperatures.